2009
DOI: 10.1590/s0066-782x2009000900010
|View full text |Cite
|
Sign up to set email alerts
|

Índice de massa corporal apresenta boa correlação com o perfil pró-aterosclerótico em crianças e adolescentes

Abstract: Background: More recently, the association of different risk factors has been described as the metabolic syndrome. Different definitions are being used for the same syndrome. Regardless of the name or classification, it has been well established that a cardiovascular cluster including overweight/obesity, increased blood pressure, and lipid and glucose abnormalities are associated with an increased risk of atherosclerosis in adults.Objective: The aim of this study was to correlate body mass index percentiles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
2
6
0
2
Order By: Relevance
“…A positive association between BMI and HOMA-IR in children and adolescents has been shown in several studies [42,43], while there was no correlation between current BMI and insulin resistance in the present study. The main reason for no correlation between two parameters might be due to the narrow BMI range, because the subjects in this study were limited to overweight.…”
Section: Discussionsupporting
confidence: 55%
“…A positive association between BMI and HOMA-IR in children and adolescents has been shown in several studies [42,43], while there was no correlation between current BMI and insulin resistance in the present study. The main reason for no correlation between two parameters might be due to the narrow BMI range, because the subjects in this study were limited to overweight.…”
Section: Discussionsupporting
confidence: 55%
“…Adipokines such as leptin and plasminogen activator inhibitor type 1 are mostly produced by visceral adipose tissue. These adipokines play important regulatory roles in a variety of biological processes, including insulin resistance and atherosclerosis [31-36]. Indulekha K et al [37] reported that visceral fat accumulated with increasing glucose intolerance and was associated with decreased levels of adiponectin and increased levels of high sensitive C-reactive protein, tumor necrosis factor-alpha, oxidized LDL, HOMA-IR and CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio de Costa et al mostró cómo el porcentaje de IMC en niños y adolescentes, distribuido por cuartiles, se asoció con diferentes factores de riesgo cardiovascular, entre ellos, la concentración de TG, cuyo promedio se incrementó a medida que aquel lo hacía, como también el c-HDL, cuya concentración disminuyó con el aumento en el porcentaje del IMC 24 . En nuestro estudio se observaron resultados similares en las niñas, quienes incrementaron los valores de TG a medida que se alteró el IMC, y el valor de c-HDL disminuyó al comparar las niñas obesas con las que presentaron un IMC adecuado.…”
Section: Discussionunclassified